The effects of surface composition on 6-weeks of plyometric training - Addie, C. D.; Farley, R. S.; Stevens, S. L.; Brandt, H. J.; Arnett, J. E.; Caputo, J. L. (International Journal of Kinesiology & Sports Science, 2022)
Background: Plyometric training programs may be performed on a hard surface or a soft surface to target specific training adaptations and enhance jump performance. However, it is unknown how surface compliance impacts jump performance. Objective: To compare changes in horizontal lower body power following a 6-week plyometric training program performed on a soft surface (n = 9) and a hard surface (n = 11). Methods: This was a quasi-experimental study. University students (N = 20; males = 11, females = 9; age: 20.4 ± 3.7 yr; body mass: 68.4 ± 12.5 kg; height 1.7 ± 0.1 m) with a history of being physically active volunteered to participate. Participants performed an initial pre-test standing long jump (SLJ), measured in centimeters (cm), then went through an accommodation period to be familiarized with training demands. A post-accommodation pre-test for SLJ was then completed. After the accommodation period, a 6-week plyometric training program was conducted. Following the completion of the training, a post-test was performed. The SLJ distance was analyzed with a 2 (surface) x 2 (time) repeated measures ANOVA. Results: There was no interaction for surface, but there was a main effect for time. Both training groups improved jump distance from pre- (soft surface = 191.6 ± 34.6 cm, hard surface = 216.1 ± 25.4 cm) to post-test (soft surface = 205.7 ± 38.8 cm, hard surface = 227.2 ± 23.4 cm). Conclusion: Practitioners designing plyometric training programs to increase lower body horizontal power may perform the training sessions on a soft surface or a hard surface and see similar improvements in horizontal jump performance.